The role of emotional intelligence in consumer responses to advertising - Antunes, Ana Cristina (2020)
Individual differences can lead to changes in the responses given towards an advertising appeal. This is an exploratory study that analyses the influence of emotional intelligence, need for cognition and need for emotion in the consumers’ response to advertising. The results confirm the importance of considering emotional intelligence as an important factor to predict the global opinion towards the ad, the attitude towards the ad and the emotional responses to advertising. The influence of need for cognition and need for emotion in the emotional responses to advertising is also discussed.